Research of the Electron Gun Cathode Tracking System - Jukna, T.; Sinkevičius, V.; Šumskienė, L.; Viržonis, D. (Elektronika ir Elektrotechnika, 2005)
The electron gun cathode tracking system measures the distance between the modulator and accelerating electrode, calculates the distance between the surface of the cathode and the modulator so, that the cut-off voltages of all three electron beams are equal. The cathode position is measured by the means of mechanically contacting probe. During the measurement process the compensational force, produced by the compressed air, is being applied to the probe in order to avoid the damage of the surface of the cathode. An additional source of mechanical vibrations is used to reduce the still friction force. Ill. 13, bibl. 3 (in Lithuanian; abstracts in Lithuanian, English and Russian).